Wuzhishan miniature pig-derived intestinal 2D monolayer organoids to investigate the enteric coronavirus infection - Yuanyuan Liu; Yuanyuan Liu; Yuanyuan Liu; Ning Yang; Ning Yang; Chen Tan; Chen Tan; Chen Tan; Yunhang Zhang; Yunhang Zhang; Yunhang Zhang; Shuai Gao; et al. (Frontiers in Veterinary Science)
Intestinal organoids are valuable tools for investigating intestinal physiology and pathology ex vivo. In previous studies, intestinal organoids of commercial pigs have been developed. Here, we established intestinal organoids derived from Wuzhishan miniature pigs (WZS pigs), a unique kind of pig in the Hainan province of China. Three-dimensional (3D) intestinal organoids and organoid monolayers were developed and assessed. Furthermore, the susceptibility of organoid monolayers of WZS pigs to transmissible gastroenteritis virus (TGEV) was demonstrated. An RNA-seq analysis revealed that the TGEV infection stimulated antiviral and inflammatory immune responses in organoid monolayer models. The study implied the transmission risk of swine enteric coronavirus on WZS pigs and provided useful tools for further research on WZS pigs as laboratory miniature pig models.